1984
DOI: 10.1111/j.1365-2125.1984.tb02475.x
|View full text |Cite
|
Sign up to set email alerts
|

The action of prazosin and propylene glycol on methoxamine‐induced bronchoconstriction in asthmatic subjects.

Abstract: The effect of 1 mg inhaled prazosin on bronchoconstriction induced by methoxamine was investigated in seven asthmatic subjects. Prazosin caused significant inhibition of the methoxamine‐induced bronchoconstriction in six of the seven patients. These findings suggest that methoxamine produces bronchoconstriction in asthmatic subjects via stimulation of alpha‐adrenoceptors. In previous studies propylene glycol has been used as a vehicle for delivery of prazosin. This substance was found to cause significant inhi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
7
0

Year Published

1985
1985
2013
2013

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 11 publications
2
7
0
Order By: Relevance
“…␣ 1 -Adrenergic responsiveness. Our study showed airway vascular hyperresponsiveness to methoxamine in asthmatic subjects, similar to the previously demonstrated airway hyperresponsiveness to ␣-adrenergic agonists (7,23). The mechanisms responsible for the asthma-associated smooth muscle hyperresponsiveness are not known.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…␣ 1 -Adrenergic responsiveness. Our study showed airway vascular hyperresponsiveness to methoxamine in asthmatic subjects, similar to the previously demonstrated airway hyperresponsiveness to ␣-adrenergic agonists (7,23). The mechanisms responsible for the asthma-associated smooth muscle hyperresponsiveness are not known.…”
Section: Discussionsupporting
confidence: 89%
“…There appear to be differences in the adrenergic responsiveness of airway smooth muscle between healthy and asthmatic subjects. For example, several investigators have reported that inhaled ␣ 1 -adrenergic agonists cause airflow obstruction in patients with asthma but not in healthy subjects (7,23). Conversely, ␤ 2 -adrenergic agonist-induced bronchodilation may be blunted in some patients with asthma, although the clinical significance of this defect has been called into question (4,6,16,24,25).…”
mentioning
confidence: 99%
“…All subjects visited the laboratory on two to three occasions at the same time of day within a 2 week period. On the first occasion a methoxamine challenge was carried out as has been previously described (Black et al, 1982(Black et al, , 1984 following placebo pretreatment of 0.9% w/v saline. Briefly, resting forced expiratory volume in 1 s (FEV1) and forced vital capacity (FVC) were measured using a dry vitalograph spirometer and following this, 2 ml of 0.9% w/v saline were administered over approximately 10 min using a Hudson's nebulizer with a flow rate of 6-7 /min.…”
Section: Methodsmentioning
confidence: 99%
“…All subjects visited the laboratory on two to three occasions at the same time of day within a 2 week period. On the first occasion a methoxamine challenge was carried out as has been previously described (Black et al, 1982(Black et al, , 1984 been recorded, the methoxamine challenge was commenced. On the third day 2 ml of DSCG (20 mg) was administered via a Hudson's nebulizer before the methoxamine challenge.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation